SEED PRIMING TECHNIQUES FOR DROUGHT TOLERANCE AND ITS EFFECT ON GROWTH OF HYBRID CASTOR - M. Thiruppathi; R. Kavitha; K. Thanunathan (Innovations in Agriculture)
A study was conducted to estimate the effect of seed priming techniques on germination and growth performance of castor. The seeds were subjected to priming in different concentration (1, 2 and 3 %) of solution viz., ZnSo4, Kc1 , KH2PO4, CaCl2,Cowdung slurry and water along with unprimed dry seed as a control. The result revealed that percentage of seed germination, germination index, speed of germination, seed vigour index, seedling shoot and root length, seedling root volume, seedling root and shoot dry weight and relative water content of castor were significantly higher with 2 per cent ZnSo4 primed seed, Hydropriming with 2 per cent ZnSo4 is the most promising priming technique for enhancing seedling characters and drought tolerance.